Ventricular Assist Device Support as a Bridge to Transplantation in Pediatric Patients - Dipchand, Anne I.; Kirk, Richard; Naftel, David C.; Pruitt, Elizabeth; Blume, Elizabeth D.; Morrow, Robert; Rosenthal, David; Auerbach, Scott; Richmond, Marc E.; Kirklin, James K. (Journal of the American College of Cardiology, 2018)
Pediatric ventricular assist device (VAD) use has evolved dramatically over the last 2 decades. This study sought to describe the evolution of VAD support to heart transplantation (HTx) in children in a large international multicenter cohort. Using data from the Pediatric Heart Transplant Study, comparisons were made between children (<18 years) supported to HTx (January 1, 1993 to December 31, 2015) with VAD or extracorporeal membrane oxygenation (ECMO) to VAD support. Of 7,135 listed patients, 5,145 underwent HTx; 995 (19.3%) were supported by a VAD (113 with congenital heart disease [CHD]). Patients with a VAD as their first device (n = 821) were older, larger, and more likely to have cardiomyopathy (80%) than patients transitioned from ECMO to VAD (n = 164). In the VAD-only cohort, 79% underwent HTx and 14% died, compared with 69% and 24% in the ECMO-to-VAD cohort, respectively. Patients with cardiomyopathy achieved HTx 84% of the time, with a 9% waitlist mortality rate compared with 55% and 36%, respectively, for CHD. Among VAD-treated patients, 79% were age >10 years in the earliest era, a percentage decreasing to 34% more recently, though neonates still represent <1%. Overall, survival at 2 and 20 years showed no difference between VAD and no support (2 years: 75% vs. 80%; 20 years: 55% vs. 54%). Post-HTx outcomes were better for durable versus temporary VADs (p < 0.01) and for continuous versus pulsatile VADs (p < 0.01) from 2005 onward; timing of VAD had no impact on post-HTx survival (p = 0.65). For one-quarter of a century, major advances have occurred in mechanical support technology for children, thereby expanding the capability to bridge to HTx without compromising post-HTx outcomes. Significant challenges remain, especially for neonates and patients with CHD, but ongoing innovation portends improved methods of support during the next decade. [Display omitted]